PENGEMBANGAN SISTEM KEAMANAN JARINGAN WIFI BERBASIS MIKROTIK MENGGUNAKAN METODE NETWORK DEVELOPMENT LIFE CYCLE (NDLC) (Teknosia, 2023)
In this increasingly developing era, computer technology is increasing so fast. In today's increasing technology, computer networks are widely used in all fields. However, with the increasing internet network, it will be directly proportional to the security holes used. As experienced by the internet network in the Semidang Lagan Bengkulu Tengah Sub-district Office, which is vulnerable to infiltration and the large number of users outside of employees and staff. The research method that will be applied in this study is the Network Development Life Cycle (NDLC). Several stages in this research include:: Analysis, Design, Simulation Prototyping, Implementation, Monitoring and Management. The result of this research is the development of a hotspot-based network security system to enhance network security at the Semidang Lagan Bengkulu Tengah Sub-district office. Based on the results of several tests carried out, the authors conclude that after implementing hotspot-based security development and dividing bandwidth limitations for each user account, where one account can only be used by 2 users so as to make users more controlled and overload does not occur.